2015
DOI: 10.1007/s40519-015-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Eating pathology in medical students in Eastern Germany: comparison with general population and a sample at the time of the German reunification

Abstract: Twenty years after the Reunification, an acculturation to Western beauty ideals seems to be more pronounced in female than in male medical students. Still, as a group, medical students from the newly formed German states did not appear to display a particular risk to develop eating disorders. However, due to the low response rate, results of this study should be interpreted cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The most similar study to ours was published by Weigel et al (2016) from East Germany. The subjects were medical students and compared the situation before and after the political change.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The most similar study to ours was published by Weigel et al (2016) from East Germany. The subjects were medical students and compared the situation before and after the political change.…”
Section: Discussionsupporting
confidence: 81%
“…An interesting survey was carried out among medical students in Germany (Weigel, Hofmeister, Pr€ obster, Br€ ahler & Gumz, 2016). There were 316 medical students (232 female and 84 male) from the newly formed German states who were assessed by the EDI-2 and the General Health Questionnaire-28.…”
Section: Changes In the Characteristics Of Eating Disorders Over Timementioning
confidence: 99%
“…A total of 28 independent studies [ 24 , 65 – 91 ] (28 cross-sectional studies, 35 subgroups, i.e., multiple tools, or multiple data points) comprising 21,383 participants from 20 countries were included in the analyses. The countries were: Austria N = 2; Egypt N = 1; France N = 2; Germany N = 2; Hungary N = 4; India N = 5; Korea N = 1; Lebanon N = 4; Malaysia N = 1; Malaysia N = 1; Mexico N = 1; Morocco N = 1; Norway N = 1; Palestine N = 2; Poland N = 1; Romania N = 1; Saudi Arabia N = 2; Spain N = 1; Thailand N = 1; and United States N = 1.…”
Section: Resultsmentioning
confidence: 99%
“…This might be explained by the fact that FEDs is a global problem, and as the world's population and westernization expand, so do reports of FEDs in non-Western cultures. Consistent with this finding, Weigel et al found that medical students from the newly formed German states reported higher levels of drive for thinness and body dissatisfaction as compared to a historical sample of East German medical students, suggesting "an acculturation to Western beauty ideals" [91]. In the same line, a meta-analysis of 94 studies using the EDI by Podar and Allik found more pronounced symptoms of eating disorders in non-Western than Western participants [104].…”
Section: Events Per 100 Observationsmentioning
confidence: 87%
“…Approximately 15% of female medical students in the United States have an eating disorder history, 6 and 31.4% of firstand second-year allied healthcare undergraduates in a Lebanese medical university had EDs. 7 These disorders are more prevalent in females because of their desire to be thin, dissatisfaction with their physical appearance, 8 and media pressure to achieve an ideal perfect body. 9 Preventive measures, such as education, screening, and the early detection of eating disorders 9,10 are needed to address future physicians' vulnerability to an ailment that could interfere with their medical judgment.…”
Section: Introductionmentioning
confidence: 99%